Inhibitory Effects of Ketamine on Lipopolysaccharide-Induced Microglial Activation - Yi Chang; Jie-Jen Lee; Cheng-Ying Hsieh; George Hsiao; Duen-Suey Chou; Joen-Rong Sheu (Mediators of Inflammation, 2009)
Microglia activated in response to brain injury release neurotoxic factors including nitric oxide (NO) and proinflammatory cytokines such as tumor necrosis factor-α (TNF-α) and interleukin-1β (IL-1β). Ketamine, an anesthetic induction agent, is generally reserved for use in patients with severe hypotension or respiratory depression. In this study, we found that ketamine (100 and 250 μM) concentration-dependently inhibited lipopolysaccharide (LPS)-induced NO and IL-1β release in primary cultured microglia. However, ketamine (100 and 250 μM) did not significantly inhibit the LPS-induced TNF-α production in microglia, except at the higher concentration (500 μM). Further study of the molecular mechanisms revealed that ketamine markedly inhibited extracellular signal-regulated kinase (ERK1/2) phosphorylation but not c-Jun N-terminal kinase or p38 mitogen-activated protein kinase stimulated by LPS in microglia. These results suggest that microglial inactivation by ketamine is at least partially due to inhibition of ERK1/2 phosphorylation.